Comparative Analysis of Coping Strategies and Psychological Wellbeing among Security Service Personnel of Different Age Groups - Manish Negi; Dr. Abhinav Gaur (International Journal of Indian Psychȯlogy, 2024)
The study explores the three types of coping strategies (Problem Focused Coping, Emotion-Focused Coping and Avoidant Coping) and PWB of security service personnel with varying lengths of service experience, aiming to understand how service duration influences these critical psychological aspects. By comparing personnel with different service tenures, this study seeks to identify patterns and differences that can inform targeted mental health for security service professionals. The findings reveal significant differences in coping strategies and PWB among security service personnel with different lengths of service providing insights into tailored interventions for enhancing the mental health of security personnel.